Association Between Obesity and Perioperative Morbidity in Open Versus Laparoscopic Sacrocolpopexy. Issue 2 (March 2017) - Halder, Gabriela E.; Salemi, Jason L.; Hart, Stuart; Mikhail, Emad
Abstract : Objectives: The aim of this study was to compare differences in 30-day perioperative morbidity and mortality for women undergoing open sacrocolpopexy (OSCP) versus laparoscopic sacrocolpopexy (LSCP) across all body mass index (BMI) groups and between patients of ideal versus elevated BMI (includes overweight, obese, and morbidly obese). Materials and Methods: Data for this retrospective review were obtained from the American College of Surgeons-National Surgical Quality Improvement Project database using current procedural terminology. All women older than 18 years who underwent an OSCP or LSCP from 2005 to 2013 were included. Patients were divided into 4 BMI (weight [kg]/[height (m)] 2 ) subgroups: (1) less than 25, (2) 25 to 29.9, (3) 30 to 39.9, and (4) 40 or greater. The data were analyzed using Student t or χ 2 test and Fisher exact test. Results: A total of 4894 women underwent an OSCP or LSCP. Shorter operative times were observed with OSCP ( P < 0.05) in all BMI groups except morbidly obese patients. Compared with patients of ideal body weight, overweight and obese patients had significantly longer operation times during LSCP ( P < 0.05), a difference that was not observed during OSCP. For all BMI subgroups, the length of hospital stay was significantly shorter for LSCP (1 [1–1]) versus OSCP (2 [2–3]) ( P < 0.05). Statistically significant increases in the rate of superficial surgical site infections were observed in OSCP in patients of both ideal and overweight BMIs ( P < 0.05). Conclusions: Obesity increases the operative time during LSCP. For patients in all BMI groups, LSCP offers the benefit of shorter hospital stays when compared with OSCP.